Studying the Beneficial Indicators of Intercropping of Safflower (Carthamus tinctorius L.) with Chickpea (Cicer arietinum L.), Lentil (Lens culinaris Medik), and Bitter Vetch (Lathyrus sativus L.) - Amin Yari; Farzad Mondani; Alireza Bagheri; Hamid Reza Chaghazardi (بوم شناسی کشاورزی)
Introduction[1] Intercropping is an agroecological technique in which two or more species are grown in the same area for a certain period of time. These species should be complementary to each other regarding the use of productive resources. By selecting crop species with different growth habits and minimal competition, intercropping optimizes resource absorption, resulting in improved yields compared to monoculture. Many studies have shown that intercropping systems improve the resources used, stability of production, and increased profitability per area. The aim of this study was to evaluate the beneficial indicators of intercropping of safflower, an important oil plant, with three legume species, including chickpea, lentil, and bitter vetch, under Kermanshah climatic conditions. Materials and Methods A split plots experiment was done based on a completely randomized block design in three replications in dryland conditions at the research farm of the Campus of Agriculture and Natural Resources, Razi University, during 2018-2019. In this study, chickpea, lentil, and bitter vetch were assigned to the main plots, and five intercropping arrangements included legume monoculture, 75:25 ratio of safflower and legume, 50:50 ratio of safflower and legume, 25:75 ratio of safflower and legume, and safflower monoculture were assigned to the subplots. In this research, safflower was the main crop, and chickpeas, lentils, and bitter vetch were considered as alternative crops. The beneficial indicators of intercropping, including Land Equivalent Ratio (LER), Relative Crowding Coefficient (RCC), System Productivity Index (SPI), and Actual Yield Loss (AYL) were calculated. The LER indicates the amount of land required for the crop in monoculture in order to achieve a similar yield as intercropping. The RCC indicates the competitive ability of crops grown in intercropping. In other words, it expresses the relative dominance of one species over others in intercropping. The SPI data are calculated by standardizing the alternative crop based on the main crop, whose higher values indicate the enhanced efficiency of the intercropping system. The AYL indicates the decrease or increase in the yield of intercropping compared to monoculture. The data were analyzed using ANOVA, and the means were compared with the LSD test. Results and Discussion The results showed that the LER in intercropping with chickpeas and lentils was higher than that in other treatments. Regardless of legume species, among the cultivation patterns, the 50:50 ratio of safflower and legume was superior in terms of LER (1.26) and competition index (RCC=4.6) compared to other intercropping patterns. The amount of actual yield reduction was positive for all intercropping patterns, but in the conditions where the chickpeas were cultivated as a companion crop in the intercropping, it was significantly more than the condition where the bitter vetch was cultivated as a companion crop (AYL=0.62). The highest productivity index in intercropping patterns was obtained when lentils were cultivated together with safflower (6089). The advantage of intercropping has been reported in many studies, especially those in which one of the components of intercropping is legume species, and the results of the current research are consistent with them. Intercropping provided better growth conditions for safflower compared to its monoculture. The different morphology of safflower compared to chickpea, lentil, and bitter vetch allows for minimal competition for resource uptake. The nitrogen fixation ability and facilitative effects of these legume species improved the indicators of intercropping profitability and ultimately increased safflower yield compared to its monoculture. Conclusion Regardless of the intercropping arrangements, the results of this study generally showed that the cultivation of chickpea together with safflower compared to lentil and bitter vetch resulted in more benefits in terms of the investigated intercropping indices. This was evident as the chickpea-safflower intercropping achieved the highest LERatio (1.14). This result was due to the presence of facilitative effects in chickpeas, especially their ability to biologically nitrogen fixation. With regard to the beneficial indicators of intercropping, the 50% safflower: 50% legumes pattern demonstrated superiority compared to other investigated patterns. Therefore, if the results of this study are confirmed in other years and regions under dryland conditions, the chickpea-safflower intercropping with a 50:50 pattern is recommended.